Corporate Cash Holdings and Financial Constraints —An Analysis Based on Data on China at Company Level after the Global Financial Crisis. Issue 7 (27th May 2020) - Zhang, Hong; Zhang, Yuyao; Zhou, Shimin; He, Yanmin
ABSTRACT: This paper analyses cash flow sensitivities of cash of the Chinese listed companies after the global financial crisis using System GMM Estimation based on data of listed companies in 2009–2014. This paper focuses on the firm heterogeneity of Chinese enterprises, such as financial constraints, firm sizes and cash dividends, and examines the mechanism involved in the corporate cash flow sensitivity of cash. In particular, the empirical result found that the sign of cash flows has a great impact on the cash flow sensitivity of cash. That is, a positive cash flow of a company has a negative and significant effect on the cash flow sensitivity of cash, while the effect of a negative cash flow is positive. Moreover, working capital influences the corporate cash-holding level. The more the working capital is, the less the cash-holding level becomes. Furthermore, disposals of fixed assets have positive influences on the cash flow sensitivity of cash.